Goal Setting and Raising the Bar: A Field Experiment - Max van Lent; Michiel Souverijn (Tinbergen Institute, 2017)
We study goal setting using a randomized field experiment involving 1092 first-year undergraduate students. Students have private mentor-student meetings during the year. We instructed a random subset of mentors to encourage students to set a course-specific grade goal during one of the mentor-student meetings (goal treatment). A random subset of those mentors was further instructed to challenge students to set more ambitious goals if deemed appropriate (raise treatment). We find that students in the goal treatment perform significantly better as compared to students in the control group, and more so when they performed poorly prior to the experiment. Next, we find that students in the raise treatment do not perform significantly different from the control group. Finally, students who set a goal and are challenged to set a more ambitious goal perform significantly worse than comparable students in the goal treatment.
Keywords: C93; I23; 330; Goal setting; motivation; education; field experiments